Laboratory Evaluations of Syzygium aromaticum (L.) Merr. et Perry Essential Oil Against Varroa destructor - Maggi, Matías Daniel (2010)
The oil obtained by hydrodistillation of the floral bottom of Syzygium aromaticum (L.) Merr. et Perry was analyzed by GC and GC/MS. Eugenol was the main constituent in the oil (86.7%). The biological activity of the oil applied to Varroa destructor and Apis mellifera was evaluated in two laboratory tests. Mite lethality was estimated using a complete exposure method test with the oil at different concentrations, and a systemic administration method of oil at different concentrations diluted in syrup was placed in feeders for bees. The LC50 for complete exposure method at 24 h was 0.59 mL/dish. The inferior and superior limits obtained were 0.47 x 10-6 mL/dish and 1.22 mL/dish, respectively. LC50 estimated at 48 h showed a slight decrease as compared to that recorded at 24 h. Ratio selection (LC50 of A. mellifera/ LC50 of V. destructor) for complete exposure method was 26.46 and 13.35 for 24 h and 48 h, respectively. Regarding the systemic administration method, mites LC50 at 24 h was 12,300 ppm. The inferior and superior limits calculated were 9,214 ppm and 15,178 ppm, respectively. LC50 estimated at 48 h showed a slight decrease as compared to that recorded at 24 h. Ratio selection for systemic administration method was 3.05 and 2.22 for 24 h and 48 h, respectively. Syzygium aromaticum oil was found to be an attractant for V. destructor at 4.8% (w/w) concentration. The results showed that oil toxicity against V. destructor differed depending upon its administration. Nevertheless, the ratio selection calculated by this oil is expected to enable its application under field conditions with a good safety margin. This oil could also be used in combination with other oils in integrated pest management strategies in bee colonies.